Recommendations of the Polish Society of Physiotherapy, the Polish Society of Family Medicine and the College of Family Physicians in Poland in the field of physiotherapy of back pain syndromes in primary health care - Kassolik, Krzysztof; Rajkowska-Labon, Elżbieta; Tomasik, Tomasz; Pisula-Lewadowska, Agnieszka; Gieremek, Krzysztof; Andrzejewski, Waldemar; Dobrzycka, Anna; Kurpas, Donata (Family Medicine & Primary Care Review, 2017)
The purpose of these guidelines is to attract attention to the need for systemic corrections in the existing health care model to become an effective tool for improving health. The intention of the authors is to present the assumptions of a new approach of physiotherapeutic treatment standards for patients with motor disorders in back pain syndromes: cervical, thoracic and lumbar-sacral, at the primary health care level. The current management provides care for this group of primary care patients mainly through pharmacotherapy and/or by referring them to an appropriate specialist outpatient clinic. In the latter situation, the waiting time from the appearance of pain to first contact with the physiotherapist in Poland is several months. In many patients, the symptoms of back pain are uncomplicated and require a few simple low-cost physiotherapeutic procedures (massage, simple physical therapy and kinesis therapy). In such cases, physiotherapeutic treatment should be based on the simple assessment of the patient’s condition and planning therapy on this basis. This can be achieved by performing a functional examination and palpation assessment to determine which muscles and ligaments are responsible for pain. This evaluation provides a basis for establishing a physiotherapeutic strategy based on massage, physical therapy and kinesitherapy. In addition, simple instruction on self-massage, self-physiotherapy and self-kinesitherapy should be provided, as well as the need for orthotic supplies and other technical assistance ought to be considered. The potential effects of such a form of primary care activation include: increase of the possibility to have influence, using directed simple physical factors, on a particular motion system disorder by the patient himself/herself, support of the rehabilitation process performed by a physiotherapist in the primary care and specialist outpatient clinic setting and shaping conscious pro-health attitudes in primary care patients.